Factors Affecting the Operational Efficiency of the Village and Urban Community Fund of Wanon Niwat District Sakon Nakhon Province - Ratana, Watchara; Romyen, Lamai; Swasthaisong, Sanyasorn (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The Village Fund aims to be a source of revolving funds for investment to develop careers, create jobs, generate income, increase income, and reduce expenses, or for promotion and development towards creating welfare or any other common benefits for the people in villages or urban communities. Including being a source of revolving funds to alleviate urgent problems for people in villages or urban communities. Thus, the purposes of this study included the following: 1) To study the level of strategic leadership public participation and efficiency of village and urban community fund operations in Wanonniwat District 2) To study the influence of strategic leadership and public participation that affects the efficiency of village and urban community fund operations in Wanonniwat District. Methodology: The sample group included village and urban community fund members in Wanonniwat District, in Sakon Nakhon Province, 395 people, used a questionnaire as a tool to collect data. Statistics used in data analysis include frequency, percentage, average, and standard deviation, and multiple regression analysis. Results: (1) Strategic leadership of village leaders in Wanonniwat District Overall, it is at a high level. People's participation in the village and urban community fund operations of Wanonniwat District. Overall, it is at a high level. and the efficiency of the village and urban community fund operations of Wanonniwat District Overall, it is at a high level. (2) Strategic leadership in controlling the organization in balance (β=.320), acting with morality (β=.315), setting strategic direction (β=.180), and supporting effective organizational culture ( β=.147) has an influence on strategic leadership that affects the operational efficiency of village and urban funds with statistical significance at the .01 level. They were able to jointly predict the operational efficiency level of village and urban funds in Wanonniwat District at 70.80 percent (R2Adj=.708). 3) public participation Participation in receiving benefits (β=.436) and participation in evaluation (β=.178) influence strategic leadership that affects the efficiency of village and urban community fund operations. Statistically significant at the .01 level, participation in decision-making (β=.123) has an influence on strategic leadership that affects the efficiency of village and urban community fund operations. Statistically significant at the .05 level. Together they were able to predict the operational efficiency level of the Village and Urban Fund in Wanon Niwat District at 46.60 percent (R2Adj=.466). Conclusion: The study illuminates a positive landscape in Wanonniwat District, where strategic leadership among village leaders and active public participation play pivotal roles in driving the high operational efficiency of village and urban community funds. The identified factors, including balanced organizational control, moral conduct, and robust support for organizational culture, underscore the interconnectedness of strategic leadership with effective fund operations. Public involvement, particularly in benefits reception, evaluation, and decision-making processes, further contributes significantly to the overall operational efficiency. These findings collectively underscore the holistic and collaborative nature of leadership and community engagement in ensuring the success of village and urban community fund operations in Wanonniwat District.